Homosexuality and the crisis of Anglicanism - Sachs, William L. (Cambridge University Press, 2009)
The Anglican conflict over homosexuality has drawn worldwide interest and divided the church. However, conflict within Christianity is not new. This book traces the steps by which the crisis emerged, and reveals the deeper debates within the church which underlie both the current controversy and much earlier splits. William L. Sachs contends that the present debate did not begin with opposition to homosexuality or in advocacy of it. He argues that, like past tensions, it originates in the diverging local contexts in which the faith is practised, and their differing interpretations of authority and communion. In the aftermath of colonialism, activists and reformers have taken on prominent roles for and against the status quo. The crisis reveals a Church in search of a new, global consensus about the appropriate forms of belief and mission.